Constituting Unity and Difference: Vernacular Architecture in a Minangkabau Village - Marcel Vellinga (KITLV Press, 2004)
Antropologists, architects, and those interested in Indonesian cultural history or vernacular architecture studies will value this in depth analysis of one of the country's most striking and popular building traditions.